The High-Effective Catalytic Degradation of Benzo[a]pyrene by Mn-Corrolazine Regulated by Oriented External Electric Field: Insight From DFT Study - Long, Tairen; Wan, Haiyan; Zhang, Jianqiang; Wu, Jie; Liang, Jin-Xia; Zhu, Chun (Frontiers in Chemistry, 2022)
The degradation of BaP into hydroxybenzo[a]pyrene by Mn-corrolazine and its regulation by an oriented external electronic field (OEEF) were systematically studied using first-principle calculations. Extensive density function calculations showed that the degradation of BaP into hydroxybenzo[a]pyrene by Mn-corrolazine occurs via a three-step process in the absence of OEEF, in which a more toxic and stable epoxide intermediate is generated. However, upon application of OEEF along the intrinsic Mn-O reaction axis, the degradation of BaP into hydroxybenzo[a]pyrene is greatly simplified. The negative charge on the terminal O atom of Mn-OO corrolazine increases with an increase in the OEEF intensity. As the intensity of the OEEF increases over 0.004 a.u., the negatively charged terminal O atom has the ability to directly abstract the positively charged H atom of BaP and the degradation of BaP into hydroxybenzo[a]pyrene can be completed via a one-step process, avoiding the production of more toxic epoxide intermediates.